2019
DOI: 10.3390/ma12233837
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microwave Sintering Temperature and Holding Time on Mechanical Properties and Microstructure of Si3N4/n-SiC ceramics

Abstract: The n-SiC (nanometer SiC) is added to be the additive in order to improve the mechanical performance of Si3N4 ceramics. A microwave sintered the ceramics at different temperature and holding times. The results shows that the Si3N4/n-SiC ceramics (85 wt% Si3N4 + 5 wt% n-SiC + 5 wt% Al2O3 + 5 wt% Y2O3) have the best mechanical properties at 1600 °C, which is beneficial to the densification and β-Si3N4 phase formation for 10 min: the density, hardness, and fracture toughness were 97.1%, 14.44 GPa, and 7.77 MPa·m1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…It can be considered as the β phase of SiN according to previous literature. 28 At the same time, the peak density of SiN also became intensive with the increase of SiN content while the peak of PPC declined with the decrease of its content in the PSN composite. The FTIR spectrum of PSN showed different wavenumbers of chemical structures (Fig.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…It can be considered as the β phase of SiN according to previous literature. 28 At the same time, the peak density of SiN also became intensive with the increase of SiN content while the peak of PPC declined with the decrease of its content in the PSN composite. The FTIR spectrum of PSN showed different wavenumbers of chemical structures (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…It is well known that the β phase helps SiN improve fracture toughness. 28 The biological functions of the β phase of SiN are related to enhanced cell phenotype such as antibacterial and osteogenic effects. 33 According to the European Food Safety Authority (EFSA), it has not yet been possible to establish a tolerable upper intake level (UL) and it is unlikely that even high dietary intake of Si element may cause adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Note that both surface morphology and stoichiometry have a crucial influence on the relevant mechanical and biological properties of Si 3 N 4 . For instance, it was reported that the properties of Si 3 N 4 at room temperature are controlled by the size and aspect ratio of the β-phase grains, while its strength at high-temperatures is mainly dependent on the grain boundary phase [ 11 , 34 , 35 ].…”
Section: Synthesis and Manufacturing Process Of Si 3 ...mentioning
confidence: 99%
“…In addition, SiC nanoparticles have been used as additives to improve the mechanical properties of Si 3 N 4 . Li et al [ 35 ] utilized microwave sintering, which promotes the rapid densification and refinement of the crystalline microstructure. The addition of the SiC nanoparticles not only strengthened the ceramic but also promoted the phase transformation of Si 3 N 4 .…”
Section: Mechanical Properties Of Si 3 Nmentioning
confidence: 99%
“…Currently, conventional sintering is restricted by its natural impediments of uneven temperature and long heating time, whereas microwave sintering features a fast heating speed and more uniform heating and delivers consistent temperature fields [6][7][8]. Microwave sintering technology is broadly adopted in the preparation of other materials: BCTZ piezoelectric ceramics [9], BaTiO 3 ceramics [10], lithium-ion battery electrodes (Li 2 TiO 3 ceramics) [11], ZnO-based piezoresistive materials [12], Si 3 N 4 ceramics [13], Ni-TiC composites [14], Cu-MWCNT nanocomposites [15], graphite alkene-ceramic composites [16], BaTiO 3 -Ag high-energy capacitors [17], various composite materials and hardened alloy materials [18,19], high-performance heat-resistant molybdenum materials [20], and titanium alloy materials [21]. Nevertheless, while utilizing microwave sintering, there are circumstances where the sample fails to absorb microwaves uniformly at low temperatures, leading to the results of uneven heating and potential cracks on the final products.…”
Section: Introductionmentioning
confidence: 99%